Primary cutaneous melanoma: an 18-year study (Clinics, 2010)
BACKGROUND: Primary cutaneous melanoma still constitutes the main cause of skin cancer death in developed countries, and its incidence in recent years has been increasing in a steady, worrisome manner. OBJECTIVES: This study evaluated the clinical, epidemiological and demographic aspects of this disease, and correlated them with patient prognosis. METHODS: Using epidemiologic and clinical data, we analyzed 84 patients with mild to severe primary cutaneous melanoma treated between 1990 and 2007. Slides containing surgical specimens were analyzed, and new slides were made from archived paraffin sections when necessary. RESULTS: The melanoma incidence was higher in areas of sun exposure, with lesions commonly observed in the trunk for males, and lower limbs for females. In addition to Breslow's thickness and ulceration (p = 0.043 and p < 0.001, respectively), the mitotic rate per mm² also correlated with worse patient outcome (p = 0.0007). The sum of ulceration (0 when absent or 1 when present), the Breslow index (1 when ;1 mm and ;4 mm) and the mitotic index (0 when absent or 1 when >;1 per mm²) allowed the establishment of a prognostic score: if the sum was equal to or over three, nearly all (91.7%) patients had systemic disease. The 5-year survival was approximately seventy percent. CONCLUSION: Because American Join Committee of Cancer Staging will update the classification of malignant tumors (TNM) staging in the near future, and introduce mitosis as a prognostic factor, our results show the importance of such a feature. Additional studies are necessary to confirm the importance of a prognostic score as proposed herein.